2022
DOI: 10.3389/fonc.2022.930491
|View full text |Cite
|
Sign up to set email alerts
|

Resection of the Primary Tumor Improves the Survival of Patients With Stage IV Gastric Neuroendocrine Carcinoma

Abstract: BackgroundThe prognostic prolongation effect of surgical resection in the management of gastric neuroendocrine carcinoma (GNEC) with distant metastases was still uncertain. The purpose of this study was to investigate the association of primary tumor resection (PTR) with outcomes in patients with stage IV GNEC.MethodsThis retrospective study analyzed patients with distant metastatic GNEC diagnosed between 2000 and 2018 and identified using the Surveillance, Epidemiology, and End Results (SEER) database. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…It has been shown that primary tumor resection contributes to a better prognosis compared to non-surgical treatment in patients with Stage IV gastric NECs. 28 However, the mortality rate was higher in patients with NECs. This is consistent with patients with NECs having a worse prognosis.…”
Section: Discussionmentioning
confidence: 98%
“…It has been shown that primary tumor resection contributes to a better prognosis compared to non-surgical treatment in patients with Stage IV gastric NECs. 28 However, the mortality rate was higher in patients with NECs. This is consistent with patients with NECs having a worse prognosis.…”
Section: Discussionmentioning
confidence: 98%
“…Due to its rarity, there is currently no standard treatment. Surgery remains by far the most important treatment option, and studies have shown that even patients with advanced disease may benefit from palliative primary tumor resection ( Li et al, 2022 ). However, the recurrence rate after radical surgery is as high as 45.7% ( Lin et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Cai et al of patients with colorectal NECs metastatic to the liver found that primary site surgery was associated with decreased mortality for both right‐sided and left‐sided primaries 14 . Finally, a study of the Surveillance, Epidemiology, and End Results (SEER) database by Li et al found resection of the primary tumor to improve survival in patients with metastatic gastric NEC 41 …”
Section: Discussionmentioning
confidence: 99%